A Suggested Model to Simulate the Distance Between Signalized Intersection and U-turn on Urban Road (Study Case: Middle East Ring Road, Surabaya) - Muhammad Hadid; Wahju Herijanto; Hera Widyastuti (IPTEK Journal of Proceedings Series, 2017)
U-turn movement possible generates queueing on U-turn system. Queueing which occurs near intersection could affects to intersection performance. The intersection performance that influenced is speed of vehicle to pass the intersection. The impact is interlock of intersection movement possibly occur. The objective of the research is to determine minimum distance of U-turn and intersection based on Poisson Process Simulation. Location of this research is U-turn on Surabaya, Indonesia with distance from the nearest intersection about 202 meters. Queueing will occur when arrival time of vehicle from intersection is above of total arrival time and service time of vehicle from U-turn. The result of simulation is total queuing cause of operational U-turn about  10 vehicles or 60 meters. The reduction distance of U-turn and Intersection is 142 meters, and it’s still fulfil the requirement of regulation about the distance between opening and intersection.